Camo girl - Magoon, Kekla (New York : Aladdin, 2011)
A poignant novel about a biracial girl living in the suburbs of Las Vegas examines the friendships that grow out of, and despite, her race.
600
MSBA Nominee 2012-13.
Keywords: Friendship -- Juvenile fiction; Racism -- Juvenile fiction; Racially mixed people -- Juvenile fiction